Simultaneous visualisation of calcified bone microstructure and intracortical vasculature using synchrotron X-ray phase contrast-enhanced tomography. Issue 1 (December 2017) - Núñez, Juan; Goring, Alice; Hesse, Eric; Thurner, Philipp; Schneider, Philipp; Clarkin, Claire
Abstract 3D imaging of the bone vasculature is of key importance in the understanding of skeletal disease. As blood vessels in bone are deeply encased in the calcified matrix, imaging techniques that are applicable to soft tissues are generally difficult or impossible to apply to the skeleton. While canals in cortical bone can readily be identified and characterised in X-ray computed tomographic data in 3D, the soft tissue comprising blood vessels that are putatively contained within the canal structures does not provide sufficient image contrast necessary for image segmentation. Here, we report an approach that allows for rapid, simultaneous visualisation of calcified bone tissue and the vasculature within the calcified bone matrix. Using synchrotron X-ray phase contrast-enhanced tomography we show exemplar data with intracortical capillaries uncovered at sub-micrometre level without the need for any staining or contrast agent. Using the tibiofibular junction of 15 week-old C57BL/6 mice post mortem, we show the bone cortical porosity simultaneously along with the soft tissue comprising the vasculature. Validation with histology confirms that we can resolve individual capillaries. This imaging approach could be easily applied to other skeletal sites and transgenic models, and could improve our understanding of the role the vasculature plays in bone disease.